Building Connections and Critical Language Awareness between Learning Communities Collaborating across Two Distant States - Damián Vergara Wilson; Marisol Marcin (Languages, 2022)
Can Critical Language Awareness (CLA) be increased through sociolinguistically based student projects in learning communities collaborating across distant states? If so, how can educators detect this increase in CLA? During the spring of 2020, students in mixed learning communities (SHL/L2) at the intermediate level at two large universities collaborated through online tools to deepen their sociolinguistic understanding of the Spanish of the United States through authentic sociolinguistic data collection. The data for the current study come from interviews with four of these students and from their final reflection papers, providing participant-based depictions of their language experience including criticality and resistance to it. We find evidence that students already expressed elements of CLA before entering the class, and that they also achieved new critical insights through participating and collaborating in class projects. To identify gains in CLA conveyed by student voices, we operationalized CLA as expressions of language experience that either challenged hegemonic paradigms (e.g., stigmatization of certain forms) or identified the role of hegemonic forces in collective or individual behavior. In order to tie CLA to widespread tools used in education, we connect it to notions of the Revised Bloom’s Taxonomy. Overall, we propose observable goals that can be used to understand and assess the presence of CLA in students’ discourse.